A Monte Carlo study of old and new frontier methods for efficiency measurement - Jens Krüger (Technische Universität Darmstadt, Department of Law and Economics, 2010)
This study presents the results of an extensive Monte Carlo experiment to compare different methods of efficiency analysis. In addition to traditional parametric-stochastic and nonparametric-deterministic methods recently developed robust nonparametric-stochastic methods are considered. The experimental design comprises a wide variety of situations with different returns-to-scale regimes, substitution elasticities and outlying observations. As the results show, the new robust nonparametric-stochastic methods should not be used without cross-checking by other methods like stochastic frontier analysis or data envelopment analysis. These latter methods appear quite robust in the experiments.
Keywords: C14; D24; C15; 330; Monte Carlo experiment; efficiency measurement; nonparametric stochastic methods; Technische Effizienz; Nichtlineares Verfahren; Stochastischer Prozess; Monte-Carlo-Methode; Robustes Verfahren; Theorie